The influence of female oviposition strategy on sibling cannibalism in the ladybird beetle Harmonia axyridis (Coleoptera: Coccinellidae) - Naoya OSAWA (European Journal of Entomology, 2003)
I hypothesized that sibling cannibalism is one of maternal investment in that a female controls sibling cannibalism. To test the hypothesis, I conducted a laboratory experiment and field observations to investigate sibling cannibalism in relation to cluster size and cluster site in the ladybird beetle, Harmonia axyridis Pallas. In the laboratory experiment, cluster size significantly affected the number of cannibalized eggs per cluster (R2 = 0.516), while cluster size was significantly affected by the oviposition interval. Furthermore, there was a marginally significant positive relationship between cluster size and the percentage of sibling cannibalism per cluster. In the field, cluster size and the direct distance from a cluster site to an aphid colony (an indicator of intensity of non-sibling cannibalism) significantly affected the number of cannibalized eggs per cluster (R2 = 0.472). Furthermore, there was a significant positive relationship between the direct distance from a cluster to the nearest aphid colony and cluster size. However, there was not a significant relationship between the distance and the percentage of sibling cannibalism. These results may be caused by the weakness of the female's power to control sibling cannibalism. Thus, a female H. axyridis controls cluster size through the intensity of non-sibling cannibalism, which may be one of oviposition strategies in this species.